Elites and health infrastructure improvements in industrializing regimes - Tommy Krieger (Journal of Economic Growth, 2023)
We collect information about more than 5000 Prussian politicians, digitize administrative data on the provision of health-promoting public goods, and gather local-level information on workers' movements to study why elites in industrializing countries implement policies that improve the health of the poor. Using county-level variation in elite structure, we present OLS and IV estimates, suggesting that elites improve access to health services due to pressure exerted by workers' movements. By contrast, policies that prevent disease outbreaks are implemented without such pressure. Analyses of roll- call votes substantiate the findings of the county-level analysis.
Keywords: H11; H42; H75; I15; N33; O43; P16; 330; Distribution of power; Elite structure; Industrializing countries; Political economy of health-promoting policies; Prussian history; Redistribution; Workers' movements